Factores socioeconómicos y su impacto en la alimentación saludable de las familias del Sector Sol Brisa del cantón Babahoyo, periodo junio septiembre 2024. - Bajaña Santana, Ariel Guillermo (2024)
This research work explores the socioeconomic factors and their impact on the healthy eating habits of families in the Sol brisa sector of the Babahoyo canton, Ecuador. Demographic characteristics and labor and economic aspects that condition the quality and quantity of food consumed were identified. In addition, the level of knowledge about nutritional education and the cultural and social influences that shape eating habits were investigated. The objective was to determine the socioeconomic factors and their impact on healthy eating in the families of the Sol Brisa sector, through the proposed methodology, detailed information was obtained on income, labor stability and access to fresh food, revealing a precarious economic situation, where most households lack financial stability, which forces them to reduce the quality of their diet. The findings reflect limited access to nutritional information and lack of participation in community programs that promote healthy eating, which accentuates food vulnerability. The conclusions point to the urgent need for interventions that address both economic and educational factors, promoting sustainable strategies that enable families to improve their diets and, consequently, their overall well-being. This analysis highlights the correlation between socioeconomic conditions and dietary health, underlining the importance of developing policies that strengthen nutrition education and facilitate access to nutritious foods, adapted to the realities of the community studied.